Studies on the activation of the pre-kininogenin-kininogenin (pre-kallikrein-kallikrein) system by sulfated polysaccharides and kaolin - dos Santos, E. [UNESP]; Rothschild, Hanna A. [UNESP]; Rocha e Silva, M. [UNESP] (My University, 1979)
The activation of pre-kininogenin to kininogenin (pre-kallikrein to kallikrein) is one of the steps in the series of reactions of a complex system, linked also to fibrinolysis and coagulation, that leads to kinin release in plasma (See Cochrane et al., 1976; Wuepper, 1976; Kaplan et al., 1976; Kaplan et al., 1976). For human plasma, a test using kaolin as activator and measuring kallikrein activity with the chromogenic substrate Chromozym PK (Nα-benzoyl-prolyl-phenylalanyl-arginyl-nitroanilide, Pentapharm, Basle) is routinely employed. The purpose of this paper is to further study the mechanism of this activation, by means of different activators and using as inhibitor hexadimethrine bromide (Polybrene). Besides kaolin, sulfated polysaccharides, such as heparin and cellulose sulfate are able to activate pre-kininogenin to kininogenin. Hexadimethrine as expected, inhibited the activation by heparin and also that by cellulose sulfate. The activation by kaolin however followed a different pattern suggesting, at least partially, a different mode of action of this activator. © 1979.
Keywords: cellulose; drug derivative; heparin; kallikrein; kaolin; prekallikrein; sulfuric acid; animal; enzyme activation; metabolism; rat; Animal; Cellulose; Enzyme Activation; Heparin; Kallikreins; Kaolin; Prekallikrein; Rats; Sulfuric Acids